Development and Validation of Liquid Chromatographic Method for Estimation of Ibuprofen and Famotidine in Combined Dosage Form. (9th April 2012) - Shah, Dimal A.; Suthar, Dixita J.; Baldania, Sunil L.; Chhalotiya, Usman K.; Bhatt, Kashyap K.
Abstract : An isocratic, reversed phase-liquid-chromatographic assay method was developed for the quantitative determination of ibuprofen and famotidine in combined-dosage form. A Brownlee C18, 5 μ m column with mobile phase containing water : methanol : acetonitrile (30 : 60 : 10, v/v/v) was used. The flow rate was 1.0 mL/min, and effluents were monitored at 264 nm. The retention times of ibuprofen and famotidine were 4.9 min and 6.8 min, respectively. The linearity for ibuprofen and famotidine was in the range of 2–20 μ g/mL and 0.1–10 μ g/mL, respectively. The proposed method was validated with respect to linearity, accuracy, precision, specificity, and robustness. The method was successfully applied to the estimation of ibuprofen and famotidine in combined dosage form.